Nature and Incidence of Soil Salinity in Pali Block Western Rajasthan - Dhir, R P; Singh, N; Sharma, B K (Annals of Arid Zone, 2016)
The paper presents results of a field and laboratory study of the naturally salt affected lands in Pali Block located in the southeastern tract of western Rajasthan. It is seen that area occupied by such lands forms 25% of the total geographic area of the Block. The salinity is generally high to very high and ranges from exclusively sodium chloride type to sodium - calcium chloride-sulphate tyre. Distribution of salt affected lands appears related to the down-slope nature of the sites and poor surface drainage. Source of salts in all likelihood is the weathering crust within the area itself.